Associations of Job Strain and Occupation with Subclinical Atherosclerosis: the CARDIA Study - Greenlund, Kurt J. (2010)
PURPOSE: Although occupational factors have been associated with symptomatic ischemic heart disease, associations between job strain (low decision latitude and high psychological demands) and risk for subclinical atherosclerosis measured by coronary artery calcium (CAC) has not been assessed. METHODS: CAC was measured in 3,695 participants in the Coronary Artery Risk Development in Young Adults (CARDIA) study in 2000-01 and 2005-06. Job characteristics measured by the demand-control model (psychological demands and decision latitude) were assessed in 1987-88 and in 1995-96. Associations between non-zero CAC and prior job characteristics and occupation were assessed, adjusting for potential covariates. RESULTS: Low decision latitude, high psychological demands, and job strain at either earlier exam were not associated with a positive CAC, nor were changes in the status of these job characteristics between 1987/1988 and 1995/1996. However, participants whose jobs were classified as managerial or professional in 1995/1996 were less likely to have a positive CAC than those in laborer occupations. CONCLUSIONS: Job strain measured at two earlier time points was not related to the presence of CAC at follow-up 5 to 18 years later. The association between earlier occupation and CAC may reflect socioeconomic differences or other occupational, industrial, or labor market characteristics.